New syntaxa of Molinio-Arrhenatheretea class from Mountain Crimea (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
Two associations of the meadow vegetation were described as a new for science on the base of data from Mountain Crimea. The association Trifolio (pratensis)-Brizetum elatioris was included into new alliance Trifolio (pratensis)-Brizion elatioris. Communities of the association are formed at the places of the cut out forests. The association Helictotricho (compressi)-Bistortetum officinalis is belonged to new alliance Helictotricho (compressi)- Bistortion officinalis. Such communities’ formation is connected with karst crater conditions at the yaila’s. These syntaxa were assigned to Arrhenatheretalia order. The differences of the floristic composition in comparison of ordere phytocenoses from the plain regions have been considered. It was noted that phytocenoses of the described syntaxa need a future investigations and comparisons with similar communities from other mountain massive of Europe, Mediterranean especially.
Keywords: meadow, Arrhenatheretalia, Briza elatior, Alchemilla, afterforest vegetation, karst crater vegetation.